An analysis of the current status of geriatric oral disease treatment—a dental institutions-based perspective - Li, Caili; Huang, Dongmei; Pan, Qini; Tao, Pinyue; Pan, Xiao; Pan, Yanfei; He, Ruofei; Wang, Tongting; Huang, Huiqiao (Frontiers in Public Health, 2025)
BackgroundThis study aimed to investigate and analyze the current status of oral disease treatment among the older adult in Guangxi Zhuang Autonomous Region, while also assessing the continuing medical education (CME) needs of dental institution personnel regarding oral diseases in this population.MethodsConvenience sampling was used to investigate the oral disease treatment among older adults and to assess CME needs of dental institution personnel regarding oral diseases in this population across various oral medical and health institutions in Guangxi.ResultsA total of 754 valid questionnaires were collected, of which 70.3% were from non-public oral health institutions. Out-of-pocket costs for older adults were as high as 91.3%. The per capita cost of older adult patients was beyond 500 yuan in 51.6% of the oral health institutions. In terms of CME training, 32.8% of dental institution medical personnel have participated in CME courses specifically on oral diseases in the older adult. Meanwhile, 69.9% of institutions have expressed a need for CME training on oral diseases in the older adult.ConclusionNon-public oral health institutions account for a significant proportion, and the older adult primarily pay out-of-pocket for oral disease treatment in these facilities. The high cost of treatment may pose a significant barrier to the older adult seeking oral healthcare. Increasing CME programs targeted at geriatric oral diseases can help enhance the treatment capabilities of dental healthcare workers and improve oral health outcomes for the older adult population.